Poemas (1989)
En esta sección se presenta las obras poéticas de las siguientes autoras: Alma Justa Díaz, Nora Carbonell, Gabriela Mistral, Fanny Montoya, Mati Hernández de Palacio, Margarita Galindo Steffens